Analiza porównawcza systemów informatycznych wspomagających agencje nieruchomości - Chmielarz, Witold (Comparative analysis of the information systems supported real estate agencies, 2006)
The main goal of the article is identification and evaluation of the information systems supported real estate agencies. At the beginning specification of the research branch is presented. Next, characteristics of the typical information systems supported real estate agencies are shown. In last part of text, comparative analysis of the three selected systems of the real estate agencies is given. In the end, main directions of the real estate information systems development are outlined.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 81-91